2014
DOI: 10.3121/cmr.2013.1174
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Subdural Abscess: A Rare Complication of Decubitus Ulcer

Abstract: A male patient, aged 55 years, presented to the emergency room with complaints of bilateral upper extremity weakness. His past medical history was significant for paraplegia and neurogenic bladder from a spinal cord injury, complicated with decubitus ulcers and end-stage renal disease secondary to type II diabetes mellitus. His past surgical history was significant for posterior spine fusion with Harrington rod instrumentation at the level of T10. He developed subacute onset of bilateral upper extremity weakne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The presentation of spinal subdural empyema has been described in 3 separate stages which often, but not always, progress in chronologic order at unpredictable rates [4] [7]. Most commonly, the presenting signs and symptoms are fever, back/neck pain, and radicular pain referred to affected nerve roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation of spinal subdural empyema has been described in 3 separate stages which often, but not always, progress in chronologic order at unpredictable rates [4] [7]. Most commonly, the presenting signs and symptoms are fever, back/neck pain, and radicular pain referred to affected nerve roots.…”
Section: Discussionmentioning
confidence: 99%
“…While populations likely to develop spinal epidural abscess (SEA) such as those with chronic sinus infections or conditions promoting immunosuppression, such as diabetes mellitus, systemic malignancies, use of immunosuppressive drugs, or intravenous drug abuse are likely the most at risk patient populations to also develop SSE, this has yet to be delineated given the rarity of the pathology. The reported outcomes are varied in the literature [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…It very uncommonly localizes as a central nervous system infection that may occur secondary to a systemic infection or surgery. 2 It has been observed that Staphylococcus aureus is the most frequent causative agent and the lumbar region the most frequent site of the SSA. The common age of presentation is between 60 and 70 years.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico necesita de pruebas de imagen donde el patrón de oro es la resonancia magnética nuclear (RMN) con gadolinio para la evaluación de las infecciones vertebrales y paravertebrales pues permite localizar [5][6][7] y determinar la extensión de la lesión, valorar la compresión medular y guiar la conducta quirúrgica . Una técnica con valor agregado a la RMN convencional es la imagen de resonancia con difusión ponderada, que otorga las ventajas de poder realizarse en pacientes en falla renal con restricción para el uso de gadolinio y permite discriminar colecciones de pus de otras patologías como ser aquellas postquirúrgicas, tumores 1 quísticos o hematomas .…”
Section: Introductionunclassified
“…El procedimiento de elección es la laminectomía que dependiendo de la extensión será a uno o a varios niveles con desbridamiento de todo 6 tejido infectado. Esto debe ser realizado rápidamente puesto que constituye una emergencia neuroquirúrgica .…”
Section: Introductionunclassified